EDUCATION ON THE APPLICATION OF FOOT EXERCISES TO PREVENT FOOT ULCER IN DIABETES MELLITUS PATIENTS AT THE ELDERLY POSYANDU IN TENDA 2 - Simon, Maria Getrida; D. Wea, Lidwina; Hepilita, Yohana; S. Ningsih, Oliva; R. Eka, Angelina (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Diabetic foot ulcers (DFU) are one of the most common complications in DM patients, 15-20% of patients who experience DFU must be amputated (Fawzy et al, 2019). Preventive measures and rehabilitation measures are the basic principles of treating diabetic foot. Rehabilitation measures include integrated programs, namely evaluation of ulcers, control of metabolic conditions, wound debridement, bacterial cultures, appropriate antibiotics, rehabilitation surgery and medical rehabilitation. Preventive measures include education on foot care, diabetes shoes and foot exercises (Yudhi, 2009). This community service activity was carried out in a Tenda 2 to be precise at the Tenda 2 elderly Posyandu, Langke Rembong District, Manggarai Regency. This community service activity was carried out in several stages, the first stage was identification of the number of DM sufferers at the Elderly Posyandu Tenda 2, then during the activities of the Elderly Posyandu there would be education about the importance of foot exercises to prevent diabetic ulcers, after that a video was played while teaching the elderly how to do leg exercises.